FUTURE PROSPECTS OF ELECTRIC-HYBRID VEHICLES (International journal of artificial intelligence, 2026)
Electric-hybrid vehicles (EHV) combine internal combustion and electric propulsion to balance performance, efficiency, and sustainability. This paper examines the technological evolution, challenges, and future prospects of EHVs within the global automotive industry.